Aplicación del esquema sancionatorio aduanero implicado al tránsito de mercancías vía terrestre en el Ecuador. - Salcedo Renteria, Maria Esther (Machala : Universidad Técnica de Machala, 2023)
Smuggling is and will be one of the great problems that affect the economy of all nations, Ecuador being a country that borders two nations to the north and south, makes it a country exposed to the circulation of all kinds of merchandise, seriously affecting the development of its economy and its social development. This project was developed in order to establish the sanction scheme applicable to the case presented, analyzing each factor that allows the identification of a serious breach of the Customs Law and violates the country's economic law. In the case presented, ten types of products of unknown origin were identified, the analysis of each product through the provisions of the Ecuadorian Customs legal regulations and taking referential values from different records such as scientific articles, magazines, web pages and associated legal bodies. To matter. At the conclusion of the investigation, it was identified that according to the provisions of the Comprehensive Criminal Organic Code (COIP) and in accordance with the Organic Code of Production, Trade and Investment (COPCI), it could be determined that the merchandise having an amount greater than 10 USB of the worker and without the possession of documents that justify the legal origin of the foreign merchandise that has been inserted in the national customs territory, will be sanctioned with a custodial sentence of 3 to 5 years and a fine of up to three times the customs value. of the merchandise subject to crime.
El contrabando es y será uno de los grandes problemas que afectan a la economía de todas las naciones, Ecuador al ser un país que limita con dos naciones al norte y al sur, lo convierte en un país expuesto a la circulación de todo tipo de mercancías, afectando gravemente el desarrollo de su economía y su desarrollo social. Este proyecto se desarrolló con el fin de establecer el esquema sancionatorio aplicable al caso presentado, analizando cada factor que permita identificar una falta grave a la Ley de Aduanas y viole el derecho de economía del país. En el caso presentado se identificaron diez tipos de productos de procedencia desconocida, el análisis de cada producto a través de lo establecido en la normativa legal de Aduana del Ecuador y tomando valores referenciales diferentes registros como artículos científicos, revistas, páginas web y cuerpos legales asociados a la materia. Al concluir la investigación se identificó que según lo establecido en el Código Orgánico Integral Penal (COIP) y en concordancia con el Código Orgánico de la Producción, Comercio e Inversiones (COPCI), se pudo determinar que la mercancía al tener una cuantía superior a 10 USB del trabajador y sin la tenencia de documentos que justifique el origen legal de la mercancía extranjera que ha sido insertada en el territorio aduanero nacional, será sancionado con pena privativa de libertad de 3 a 5 años y multa de hasta tres veces el valor en aduana de la mercancía objeto de delito.
Keywords: INFRACCIONES ADUANERAS; CONTRABANDO; CONTROL ADUANERO; VALORACIÓN ADUANERA